Upaya pemeliharaan koleksi pustaka di Perpustakaan SMPN 57 PALEMBANG - Dewi Ratnasari (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2019)
Maintenance of library materials is not new to the library. This is the task of the library manager, the establishment of a library means that library materials need to be maintained and preserved for the next generation. However, the task of preservation is not easy, because library managers will be faced with 'book enemies', namely: nerds, termites, cockroaches, mice, fungi and also by humans themselves such as tearing pages, folding paper, crossing pages, etc. other. This study aims to determine how to maintain library collections so that they are durable and what factors can damage library materials, as well as the obstacles faced by librarians in the process of maintaining library collections. From the results of the study the authors found that the library collection in the library of Palembang 57 Public High School was still not maximally processed due to lack of human resources and funds in the maintenance and repair of library materials in this library. For more details the author will explain the clarity in this paper. This research was conducted by means of collecting data quantitatively, then presented descriptively in analysis. Keywords: Maintenance, Library, Constraints.